High-hardness glaze coating and preparation method thereof
By preparing composite filler and combining silicone acrylic emulsion and silicate tangerine solution, the problem of insufficient adhesion and hardness of existing glaze coatings is solved, high hardness, crack resistance and water resistance are achieved, and the comprehensive coating is improved. performance.
Patent Information
- Application Number
- CN202411534776.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The adhesion and hardness of existing glaze coatings are insufficient, and the overall performance needs to be improved, and the poor dispersion of traditional fillers in the emulsion affects the performance.
The composite filler is made of titanium dioxide, silica, bentonite and concave and concave and concave and concave and concave and concave and concave earth with pickling, high temperature alkali treatment and dodecyl methyl dihydroxyethyl ammonium bromide activation to form a hydrogen bond system to improve the Filling compactness, combining silicone acrylic emulsion and potassium silicate liquid as film forming substances, and using functional additives to improve film forming properties.
A glazed coating with high hardness, crack resistance and water resistance has been achieved, with significantly improved comprehensive performance, improved dispersion and film formation quality of the filler in the emulsion, and improved coating finish and toughness.
Smart Images

Figure BDA0005111287590000101 
Figure BDA0005111287590000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coating preparation, and in particular relates to a high-hardness glaze coating and a preparation method thereof. Background Art
[0002] As people's living standards improve, different types of wall coatings have been developed and used. Glaze coatings are a new type of architectural coating with excellent performance. They have the same texture as tile glazes and are easy to clean. They are widely used in wood products, anti-corrosion and other fields. Common glaze paints include water-based glaze paints and solvent-based glaze paints. Solvent-based glaze paints are gradually abandoned by the market due to their complex process and high pollution, while water-based glaze paints have gradually occupied the mainstream of the market.
[0003] In the prior art, for example, Chinese patent document CN110922795A provides an inorganic glaze coating for exterior walls and a preparation method thereof, comprising the following raw materials in parts by weight: 20-25 parts of sericite powder, 20-25 parts of quartz powder, 15-20 parts of white cement, 10-15 parts of mineral powder, 10-15 parts of zeolite powder, 5-10 parts of lime powder, 5-10 parts of heavy calcium powder, 1-2 parts of white carbon black, 1-2 parts of nano silicon dioxide, 1-2 parts of nano magnesium oxide, 2-5 parts of hydrophobic glue powder, 0.5-1 part of hydrophobic agent, 0.5-1 part of cellulose, and 0.3-0.5 part of alkali inhibitor; the inorganic glaze coating for exterior walls provided by the inorganic glaze coating utilizes the polymerization reaction between mineral materials to form geopolymers, which are used as the binder of the exterior wall coating, and a small amount of spraying of the above-mentioned inorganic glaze coating for exterior walls can make it form an integral body with the wall. However, it can be seen that the above-mentioned glaze coating is completely bonded to the wall by organic materials, and its adhesion needs to be further improved. Its hardness is also average, and its overall performance needs to be improved.
[0004] Chinese patent document CN112795215A provides a sand-containing glaze coating and its preparation method and application, which is prepared from the following raw materials in parts by weight: 10-20 parts of emulsion, 10-30 parts of natural sand, 5-30 parts of light calcium, 20-50 parts of filler, 0.4-1 parts of water, 12-25 parts of water, 0.1-0.6 parts of dispersant, 0.1-0.6 parts of wetting agent, 0.2-0.6 parts of defoaming agent, 0.2-2.0 parts of film-forming aid, 0.5-5 parts of titanium dioxide, 0.1-0.4 parts of pH regulator, 0.1-2.0 parts of antifreeze, The amount of the solid material is 0.1-0.6 parts, and the formula includes a specific weight of emulsion, natural sand, specific light calcium, filler and water. The natural sand is firmly wrapped in the mixture of emulsion, filler and light calcium, which improves the flatness and reduces the rough feel of the natural sand without covering the natural color of the natural sand, so that it can meet the stone imitation effect. In addition, the addition of solids can also ensure the hardness and wear resistance of the real stone paint, and reduce the cost. The formed paint film has the characteristics of strong glaze effect, good adhesion, corrosion resistance, smooth surface, full sensory, scrub resistance, moisture resistance, mildew resistance, and excellent mechanical properties. However, it can be seen that the filler used is added directly, which greatly affects the dispersion of the filler in the emulsion.
[0005] Based on this, the present invention hopes to provide an environmentally friendly glaze coating with high hardness and good comprehensive performance. Summary of the invention
[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a high-hardness glaze coating and a preparation method thereof, which has high hardness, crack resistance, water resistance, good weather resistance and excellent comprehensive performance.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a high-hardness glaze coating, which is prepared from the following raw materials in terms of mass percentage:
[0009] 20-30% fluorinated silicone acrylic emulsion, 5-20% potassium silicate liquid, 8-35% composite filler, 2-8% functional additive, 2-6% film-forming additive, 20-60% water;
[0010] The composite filler is prepared using titanium dioxide, silicon dioxide, bentonite and attapulgite as raw materials.
[0011] Preferably, the preparation of the composite filler comprises the following steps:
[0012] S1. Mix bentonite and attapulgite, crush and screen them, and then treat them with hydrochloric acid solution. After the treatment, filter, wash and dry them to obtain material I;
[0013] S2, mixing the material I obtained in step S1 with sodium hydroxide and then subjecting it to high temperature treatment, after the treatment is completed, obtaining material II;
[0014] S3, adding the material II obtained in step S2 to an aqueous solution containing dodecylmethyl dihydroxyethyl ammonium bromide, and then treating it under heating conditions. After the treatment is completed, it is first centrifuged, washed, and dried, and finally activated; after the activation is completed, material III is obtained;
[0015] S4, adding silicon dioxide to the solvent, and then adding succinic anhydride and KH550 after uniform dispersion, maintaining centrifugal stirring and heating treatment, after the treatment is completed, centrifugation, washing, and drying are performed to obtain material IV;
[0016] S5. Add titanium dioxide, material III obtained in step S3 and material IV obtained in step S4 into water, stir under heating conditions, and after the treatment, filter, dry and grind to obtain a composite filler.
[0017] Further preferably, in step S1, the mass ratio of bentonite to attapulgite is 1:1.5-2.5, and the sieve is 80-150 mesh; the concentration of the hydrochloric acid solution is 10-15wt%, the temperature of the hydrochloric acid solution treatment is room temperature, and the treatment time is 2-6h.
[0018] Further preferably, in step S2, the mass ratio of material I to sodium hydroxide is 1:0.3-0.65, the high temperature treatment temperature is 710-780°C, and the treatment time is 0.5-2h.
[0019] Further preferably, in step S3, the concentration of dodecylmethyldihydroxyethylammonium bromide is 4-8wt%, and the mass ratio of material II to dodecylmethyldihydroxyethylammonium bromide is 1:0.3-0.6; the heating treatment temperature is 50-70°C, and the treatment time is 1-6h; the activation treatment temperature is 100-110°C, and the activation time is 0.5-4h.
[0020] Further preferably, in step S4, the solvent is DMF, and the mass ratio of silica, solvent, succinic anhydride and KH550 is 1:50-70:2-3.5:5-8; the centrifugal stirring rate is 80-150 rpm; the heating treatment temperature is 30-40°C, and the treatment time is 1-6 h.
[0021] Further preferably, in step S5, the mass ratio of titanium dioxide, material III, and material IV is 1:0.4-0.7:0.5-0.9; the heating treatment temperature is 25-35°C, and the treatment time is 1-4h.
[0022] Preferably, the functional additive is selected from one or more of a dispersant, a defoamer, an antifreeze agent, a wetting agent, a pH regulator, a preservative, a mildew preventer, a leveling agent, and a thickener.
[0023] Preferably, the film-forming aid is selected from one or more of propylene glycol, ethylene glycol, and alcohol ester film-forming aids.
[0024] In a second aspect, the present invention provides a method for preparing the above-mentioned high-hardness glaze coating, characterized in that it comprises the following steps:
[0025] Mix half the weight of water, fluorinated silicone acrylic emulsion, potassium silicate liquid, functional additives and film-forming additives and stir evenly, then add the composite filler and the other half weight of water and stir evenly again.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The glaze coating provided by the present invention uses fluorinated silicone acrylic emulsion and potassium silicate liquid as film-forming materials as main film-forming substances, selects composite fillers and related additives to improve film-forming properties, so that the prepared coating has the effects of high hardness, crack resistance, water resistance, etc., and has good comprehensive performance.
[0028] The glaze coating provided by the invention uses a specific composite filler, which is prepared with titanium dioxide, silicon dioxide, bentonite and attapulgite as raw materials. Among them, titanium dioxide has excellent whiteness and hiding power, and can effectively improve the smoothness and hiding power of the coating, but it has the disadvantages of poor weather resistance and easy agglomeration. Therefore, in the present invention, while retaining the use of titanium dioxide, silicon dioxide, bentonite and attapulgite are used to reduce its dosage and improve the disadvantages caused by its use; quartz powder is often used in traditional glaze coatings. Although it can improve the hardness of glaze coatings, its density is relatively large. Large-scale use will increase the overall weight of the coating and increase the difficulty of spraying. Therefore, a small amount of silicon dioxide is used in the present invention to replace it. While controlling the use, it can also greatly improve the hardness of the glaze coating and improve weather resistance. The use of silicon dioxide itself has the problem of easy agglomeration. Therefore, in the present invention, it is anhydride-modified to introduce carboxyl groups. On the one hand, its agglomeration tendency is reduced, and on the other hand, the introduced amino groups can be efficiently compounded with the hydroxyl groups contained in the modified bentonite and attapulgite; in addition, the use of silicon dioxide will also The brittleness of the glaze coating system is increased accordingly. Therefore, the present invention introduces a clay composite mainly composed of attapulgite and bentonite, which is beneficial to improving the toughness and impact resistance of the glaze coating. During use, the present invention performs corresponding treatment on attapulgite and bentonite. Specifically, the present invention first performs acid washing on the composite of bentonite and attapulgite, which is beneficial to removing impurities and preliminarily improving the pore structure of the clay and improving the activity. Then, the material I after acid treatment is subjected to high-temperature alkali treatment, which is beneficial to improving the thermal stability and pore structure of bentonite and attapulgite, promoting the stability of the system and improving its activity. Finally, the treated material II is treated with dodecylmethyldihydroxyethylammonium bromide. On the one hand, it is hoped that the agglomeration of the clay can be further reduced. On the other hand, based on the introduced hydroxyl groups, a hydrogen bond system is formed with the modified silica and fluorinated silicone acrylic emulsion, thereby ensuring the compactness of the composite filler in the emulsion, improving the film-forming quality, and thus improving the properties of the glaze coating.
[0029] When using bentonite and attapulgite, the present invention processes the two at the same time, thereby simplifying the processing flow; in addition, the dosage of bentonite and attapulgite is preferably controlled within the range of 1:1.5 to 2.5 in the present invention, thereby ensuring good rheological properties and adhesion, and synergistically improving the comprehensive performance of the glaze coating.
[0030] In conclusion, the present invention ensures the hardness, wear resistance, weather resistance and other properties of the prepared glaze coating by optimizing the components and performing specific modifications, and has good comprehensive performance. DETAILED DESCRIPTION
[0031] Embodiments of the present invention are described in detail below. All embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0032] In the present invention, the potassium silicate liquid is DY-28, purchased from Xingtai Dayang Chemical Co., Ltd.; the fluorinated silicone acrylic emulsion is prepared with reference to the prior art, such as Example 1 of patent document CN118440552A, or with reference to Example 1 of patent document CN106632876A. Preferably, it is prepared with reference to CN106632876A.
[0033] In the embodiment of the present invention, the film-forming aid is an alcohol ester film-forming aid, preferably brand OE300, purchased from Shanghai Jiushi Chemical Co., Ltd.
[0034] In the embodiment of the present invention, attapulgite is purchased from Sishui County Yuexin Smelting and Foundry Material Factory; the dispersant brand is BYK110; the defoamer brand is BYK067; the wetting agent is an organosilicon defoamer, brand TEGO AIREX 902W; and the leveling agent brand is BYK377.
[0035] In the embodiments of the present invention, the grade of silicon dioxide is Degussa A380, purchased from Degussa Chemical Co., Ltd.; bentonite is purchased from Wuhu Shuohua New Material Technology Co., Ltd.
[0036] Other raw materials not specified were purchased from the market and are generally available to those skilled in the art.
[0037] Example 1
[0038] A high-hardness glaze coating is prepared from the following raw materials, calculated by mass percentage of 100%, including 22% fluorinated silicone acrylic emulsion, 13% potassium silicate liquid, 32% composite filler, 0.5% dispersant, 0.4% defoamer, 0.6% leveling agent, 0.6% wetting agent, 3% film-forming aid, and the balance is water.
[0039] Wherein, the preparation of the composite filler comprises the following steps:
[0040] S1. Bentonite and attapulgite were mixed in a mass ratio of 1:2, and then crushed and sieved to 100 mesh, and then treated with a 12wt% hydrochloric acid solution (room temperature, 4h). After the treatment, the mixture was filtered, washed, and dried to obtain material I;
[0041] S2, mixing the material I obtained in step S1 with sodium hydroxide in a mass ratio of 1:0.45 and then subjecting the mixture to high temperature treatment (720°C, 0.5h), to obtain material II;
[0042] S3, adding the material II obtained in step S2 to an aqueous solution (4.5wt%) containing dodecylmethyldihydroxyethylammonium bromide, and then treating it under heating conditions (68°C, 3.5h), centrifuging, washing, and drying it after the treatment, and finally activating it (102°C, 1h); after the activation, material III is obtained; wherein the mass ratio of material II to dodecylmethyldihydroxyethylammonium bromide is 1:0.35;
[0043] S4, adding silica to N,N-dimethylformamide (DMF), adding succinic anhydride and KH550 after uniform dispersion, maintaining centrifugal stirring and performing heating treatment (35°C, 2h), after the treatment is completed, centrifuging (100rpm), washing, and drying to obtain material IV; wherein the mass ratio of silica, solvent, succinic anhydride, and KH550 is 1:60:2.8:6.5;
[0044] S5. Add titanium dioxide, material III obtained in step S3 and material IV obtained in step S4 into water in a mass ratio of 1:0.5:0.65, stir under heating conditions (30°C, 2h), and after the treatment, filter, dry and grind to obtain a composite filler.
[0045] In this embodiment, a method for preparing the high-hardness glaze coating is also provided, comprising the following steps:
[0046] Mix half the mass of water, fluorinated silicone acrylic emulsion, potassium silicate liquid, functional additives (dispersant, defoamer, leveling agent, wetting agent), and film-forming additives, stir evenly, then add the composite filler and the other half the mass of water, stir evenly again.
[0047] Example 2
[0048] A high-hardness glaze coating is prepared from the following raw materials, calculated by mass percentage: 23% fluorinated silicone acrylic emulsion, 12% potassium silicate liquid, 35% composite filler, 0.5% dispersant, 0.4% defoamer, 0.6% leveling agent, 0.6% wetting agent, 3% film-forming aid, and the balance is water.
[0049] Wherein, the preparation of the composite filler comprises the following steps:
[0050] S1. Bentonite and attapulgite were mixed in a mass ratio of 1:2.2, and then crushed and sieved to 100 mesh, and then treated with 13wt% hydrochloric acid solution (room temperature, 4h). After the treatment, the mixture was filtered, washed, and dried to obtain material I;
[0051] S2, the material I obtained in step S1 is mixed evenly with sodium hydroxide in a mass ratio of 1:0.5 and then subjected to high temperature treatment (715°C, 40min). After the treatment is completed, material II is obtained;
[0052] S3, adding the material II obtained in step S2 to an aqueous solution (4.8wt%) containing dodecylmethyldihydroxyethylammonium bromide, and then treating it under heating conditions (65°C, 3h), centrifuging, washing, and drying it after the treatment, and finally activating it (105°C, 1h); after the activation, material III is obtained; wherein the mass ratio of material II to dodecylmethyldihydroxyethylammonium bromide is 1:0.35;
[0053] S4, adding silica to N, N-dimethylformamide (DMF), adding succinic anhydride and KH550 after uniform dispersion, maintaining centrifugal stirring and performing heating treatment (35°C, 1.5h), after the treatment is completed, centrifuging (100rpm), washing, and drying to obtain material IV; wherein the mass ratio of silica, solvent, succinic anhydride, and KH550 is 1:65:2.6:6.7;
[0054] S5. Add titanium dioxide, material III obtained in step S3 and material IV obtained in step S4 into water in a mass ratio of 1:0.45:0.68, stir under heating conditions (30°C, 2h), and after the treatment, filter, dry and grind to obtain a composite filler.
[0055] In this embodiment, a method for preparing the high-hardness glaze coating is also provided, comprising the following steps:
[0056] Mix half the mass of water, fluorinated silicone acrylic emulsion, potassium silicate liquid, functional additives (dispersant, defoamer, leveling agent, wetting agent), and film-forming additives, stir evenly, then add the composite filler and the other half the mass of water, stir evenly again.
[0057] Example 3
[0058] A high-hardness glaze coating is prepared from the following raw materials, calculated by mass percentage: 21% fluorinated silicone acrylic emulsion, 14% potassium silicate liquid, 33% composite filler, 0.5% dispersant, 0.4% defoamer, 0.6% leveling agent, 0.6% wetting agent, 3% film-forming aid, and the balance is water.
[0059] Wherein, the preparation of the composite filler comprises the following steps:
[0060] S1. Bentonite and attapulgite were mixed in a mass ratio of 1:2.2, and then crushed and sieved to 100 mesh, and then treated with 12wt% hydrochloric acid solution (room temperature, 4h). After the treatment, the mixture was filtered, washed, and dried to obtain material I;
[0061] S2, mixing the material I obtained in step S1 with sodium hydroxide in a mass ratio of 1:0.48 and then subjecting the mixture to high temperature treatment (725°C, 0.5h), to obtain material II;
[0062] S3, adding the material II obtained in step S2 to an aqueous solution (4.2wt%) containing dodecylmethyldihydroxyethylammonium bromide, and then treating it under heating conditions (68°C, 3.5h), centrifuging, washing, and drying it after the treatment, and finally activating it (104°C, 1h); after the activation, material III is obtained; wherein the mass ratio of material II to dodecylmethyldihydroxyethylammonium bromide is 1:0.38;
[0063] S4, adding silica to N, N-dimethylformamide (DMF), adding succinic anhydride and KH550 after uniform dispersion, maintaining centrifugal stirring and performing heating treatment (35°C, 2h), after the treatment is completed, centrifuging (100rpm), washing, and drying to obtain material IV; wherein the mass ratio of silica, solvent, succinic anhydride, and KH550 is 1:60:2.9:6.3;
[0064] S5. Add titanium dioxide, material III obtained in step S3 and material IV obtained in step S4 into water in a mass ratio of 1:0.55:0.6, and stir under heating conditions (30°C, 2h). After the treatment, filter, dry and grind to obtain a composite filler.
[0065] In this embodiment, a method for preparing the high-hardness glaze coating is also provided, comprising the following steps:
[0066] Mix half the mass of water, fluorinated silicone acrylic emulsion, potassium silicate liquid, functional additives (dispersant, defoamer, leveling agent, wetting agent), and film-forming additives, stir evenly, then add the composite filler and the other half the mass of water, stir evenly again.
[0067] Comparative Example 1
[0068] Compared with Example 1, all bentonite is used in Comparative Example 1, that is, attapulgite is also replaced by bentonite, and the rest is the same. Specifically, in this comparative example, a high-hardness glaze coating is provided, which is prepared from the following raw materials, calculated by mass percentage of 100%, including 22% fluorinated silicone acrylic emulsion, 13% potassium silicate liquid, 32% composite filler, 0.5% dispersant, 0.4% defoamer, 0.6% leveling agent, 0.6% wetting agent, 3% film-forming aid, and the balance is water.
[0069] Wherein, the preparation of the composite filler comprises the following steps:
[0070] S1, the bentonite is first crushed and sieved to 100 mesh, and then treated with a 12wt% hydrochloric acid solution (room temperature, 4h). After the treatment, it is filtered, washed, and dried to obtain material I;
[0071] S2, mixing the material I obtained in step S1 with sodium hydroxide in a mass ratio of 1:0.45 and then subjecting the mixture to high temperature treatment (720°C, 0.5h), to obtain material II;
[0072] S3, adding the material II obtained in step S2 to an aqueous solution (4.5wt%) containing dodecylmethyldihydroxyethylammonium bromide, and then treating it under heating conditions (68°C, 3.5h), centrifuging, washing, and drying it after the treatment, and finally activating it (102°C, 1h); after the activation, material III is obtained; wherein the mass ratio of material II to dodecylmethyldihydroxyethylammonium bromide is 1:0.35;
[0073] S4, adding silica to N,N-dimethylformamide (DMF), adding succinic anhydride and KH550 after uniform dispersion, maintaining centrifugal stirring and performing heating treatment (35°C, 2h), after the treatment is completed, centrifuging (100rpm), washing, and drying to obtain material IV; wherein the mass ratio of silica, solvent, succinic anhydride, and KH550 is 1:60:2.8:6.5;
[0074] S5. Add titanium dioxide, material III obtained in step S3 and material IV obtained in step S4 into water in a mass ratio of 1:0.5:0.65, stir under heating conditions (30°C, 2h), and after the treatment, filter, dry and grind to obtain a composite filler.
[0075] In this comparative example, a method for preparing the above-mentioned high-hardness glaze coating is also provided, comprising the following steps:
[0076] Mix half the mass of water, fluorinated silicone acrylic emulsion, potassium silicate liquid, functional additives (dispersant, defoamer, leveling agent, wetting agent), and film-forming additives, stir evenly, then add the composite filler and the other half the mass of water, stir evenly again.
[0077] Comparative Example 2
[0078] Compared with Example 1, all attapulgite is used in Comparative Example 2, that is, bentonite is replaced by attapulgite, and the rest is the same. Specifically, in this comparative example, a high-hardness glaze coating is provided, which is prepared from the following raw materials, calculated by mass percentage of 100%, including 22% fluorinated silicone acrylic emulsion, 13% potassium silicate liquid, 32% composite filler, 0.5% dispersant, 0.4% defoamer, 0.6% leveling agent, 0.6% wetting agent, 3% film-forming aid, and the balance is water.
[0079] Wherein, the preparation of the composite filler comprises the following steps:
[0080] S1, pulverizing and sieving the attapulgite to 100 mesh, and then treating it with a 12wt% hydrochloric acid solution (room temperature, 4h). After the treatment, filtering, washing, and drying, material I is obtained;
[0081] S2, mixing the material I obtained in step S1 with sodium hydroxide in a mass ratio of 1:0.45 and then subjecting the mixture to high temperature treatment (720°C, 0.5h), to obtain material II;
[0082] S3, adding the material II obtained in step S2 to an aqueous solution (4.5wt%) containing dodecylmethyldihydroxyethylammonium bromide, and then treating it under heating conditions (68°C, 3.5h), centrifuging, washing, and drying it after the treatment, and finally activating it (102°C, 1h); after the activation, material III is obtained; wherein the mass ratio of material II to dodecylmethyldihydroxyethylammonium bromide is 1:0.35;
[0083] S4, adding silica to N,N-dimethylformamide (DMF), adding succinic anhydride and KH550 after uniform dispersion, maintaining centrifugal stirring and performing heating treatment (35°C, 2h), after the treatment is completed, centrifuging (100rpm), washing, and drying to obtain material IV; wherein the mass ratio of silica, solvent, succinic anhydride, and KH550 is 1:60:2.8:6.5;
[0084] S5. Add titanium dioxide, material III obtained in step S3 and material IV obtained in step S4 into water in a mass ratio of 1:0.5:0.65, stir under heating conditions (30°C, 2h), and after the treatment, filter, dry and grind to obtain a composite filler.
[0085] In this comparative example, a method for preparing the above-mentioned high-hardness glaze coating is also provided, comprising the following steps:
[0086] Mix half the mass of water, fluorinated silicone acrylic emulsion, potassium silicate liquid, functional additives (dispersant, defoamer, leveling agent, wetting agent), and film-forming additives, stir evenly, then add the composite filler and the other half the mass of water, stir evenly again.
[0087] Comparative Example 3
[0088] Compared with Example 1, high temperature treatment is not performed in Comparative Example 2, that is, step S2 is omitted, and the rest are the same. Specifically, in this comparative example, a high hardness glaze coating is provided, which is prepared from the following raw materials, calculated as 100% by mass: 22% fluorinated silicone acrylic emulsion, 13% potassium silicate liquid, 32% composite filler, 0.5% dispersant, 0.4% defoamer, 0.6% leveling agent, 0.6% wetting agent, 3% film-forming aid, and the balance is water.
[0089] Wherein, the preparation of the composite filler comprises the following steps:
[0090] S1. Bentonite and attapulgite were mixed in a mass ratio of 1:2, and then crushed and sieved to 100 mesh, and then treated with a 12wt% hydrochloric acid solution (room temperature, 4h). After the treatment, the mixture was filtered, washed, and dried to obtain material I;
[0091] S2, adding the material I obtained in step S1 to an aqueous solution (4.5wt%) containing dodecylmethyldihydroxyethylammonium bromide, and then treating it under heating conditions (68°C, 3.5h), centrifuging, washing, drying, and finally activating it (102°C, 1h); after the activation, material III is obtained; wherein the mass ratio of material I to dodecylmethyldihydroxyethylammonium bromide is 1:0.35;
[0092] S3, adding silica to N, N-dimethylformamide (DMF), adding succinic anhydride and KH550 after uniform dispersion, maintaining centrifugal stirring and performing heating treatment (35°C, 2h), after the treatment is completed, centrifuging (100rpm), washing, and drying to obtain material IV; wherein the mass ratio of silica, solvent, succinic anhydride, and KH550 is 1:60:2.8:6.5;
[0093] S4. Add titanium dioxide, material III obtained in step S2 and material IV obtained in step S3 into water in a mass ratio of 1:0.5:0.65, stir under heating conditions (30°C, 2h), and after the treatment, filter, dry and grind to obtain a composite filler.
[0094] In this comparative example, a method for preparing the above-mentioned high-hardness glaze coating is also provided, comprising the following steps:
[0095] Mix half the mass of water, fluorinated silicone acrylic emulsion, potassium silicate liquid, functional additives (dispersant, defoamer, leveling agent, wetting agent), and film-forming additives, stir evenly, then add the composite filler and the other half the mass of water, stir evenly again.
[0096] Comparative Example 4
[0097] Compared with Example 1, step S4 is omitted in Comparative Example 4, and the rest are the same. Specifically, in this comparative example, a high-hardness glaze coating is provided, which is prepared from the following raw materials, calculated as 100% by mass: 22% fluorinated silicone acrylic emulsion, 13% potassium silicate liquid, 32% composite filler, 0.5% dispersant, 0.4% defoaming agent, 0.6% leveling agent, 0.6% wetting agent, 3% film-forming aid, and the balance is water.
[0098] Wherein, the preparation of the composite filler comprises the following steps:
[0099] S1. Bentonite and attapulgite were mixed in a mass ratio of 1:2, and then crushed and sieved to 100 mesh, and then treated with a 12wt% hydrochloric acid solution (room temperature, 4h). After the treatment, the mixture was filtered, washed, and dried to obtain material I;
[0100] S2, mixing the material I obtained in step S1 with sodium hydroxide in a mass ratio of 1:0.45 and then subjecting the mixture to high temperature treatment (720°C, 0.5h), to obtain material II;
[0101] S3, adding the material II obtained in step S2 to an aqueous solution (4.5wt%) containing dodecylmethyldihydroxyethylammonium bromide, and then treating it under heating conditions (68°C, 3.5h), centrifuging, washing, and drying it after the treatment, and finally activating it (102°C, 1h); after the activation, material III is obtained; wherein the mass ratio of material II to dodecylmethyldihydroxyethylammonium bromide is 1:0.35;
[0102] S4, take silicon dioxide and set aside;
[0103] S5. Add titanium dioxide, material III obtained in step S3 and silicon dioxide in step S4 into water in a mass ratio of 1:0.5:0.65, stir under heating conditions (30°C, 2h), and after the treatment, filter, dry and grind to obtain a composite filler.
[0104] In this comparative example, a method for preparing the above-mentioned high-hardness glaze coating is also provided, comprising the following steps:
[0105] Mix half the mass of water, fluorinated silicone acrylic emulsion, potassium silicate liquid, functional additives (dispersant, defoamer, leveling agent, wetting agent), and film-forming additives, stir evenly, then add the composite filler and the other half the mass of water, stir evenly again.
[0106] The glaze coatings prepared in Example 1 and Comparative Examples 1 to 4 were tested for performance as follows:
[0107] Hardness test: refer to GB / T 6739-2022.
[0108] Flexibility performance test: refer to GB / T1731-2020.
[0109] Weather resistance test: refer to GB / T 9276-1996.
[0110] Impact resistance test: refer to GB / T 1732-2020.
[0111] Water resistance test: refer to GB / T 9755-2014.
[0112] Anti-cracking test: Place the coating at 40°C for 12 hours, then at -5°C for 12 hours, and observe the coating surface.
[0113] The specific test results are shown in Table 1.
[0114] Table 1 Test results of embodiments and comparative examples
[0115]
[0116]
[0117] It can be seen from Table 1 that the glaze coating prepared by the present invention has high hardness, good toughness, good weather resistance and crack resistance, and good comprehensive performance.
[0118] It should be particularly emphasized that, although the functional additives used in the present invention only include dispersants, defoamers, leveling agents, and wetting agents, other functional additives such as mildew inhibitors and preservatives can be flexibly selected and added by those skilled in the art according to actual needs, and the description of the above embodiments does not constitute a limitation on the protection scope of the technical solution of the present invention.
[0119] The glaze coating provided by the present invention can be constructed in the following steps when used:
[0120] (1) Base treatment: remove floating dust and oil stains;
[0121] (2) Wall reinforcement: Apply a layer of odorless, environmentally friendly and water-resistant wall reinforcement agent;
[0122] (3) Seam filling: Clean the joints between different base materials, the joints of gypsum boards, cracks in walls, etc., and then fill them with anti-crack joint king;
[0123] (4) Rough leveling: For areas where the wall flatness differs by more than 3mm, use powdered water-resistant leveling putty for rough leveling;
[0124] (5) Anti-crack leveling: Use soft porcelain anti-crack treasure (two-component waterproof flexible anti-crack smooth putty) to apply twice, and control the thickness to 1-1.5mm;
[0125] (6) Fine leveling: Use wall glaze mud (paste-like water-resistant glossy putty) to apply one or two coats and grind it smooth;
[0126] (7) Bottom wall glaze: Apply one coat of white or transparent penetrating base glaze;
[0127] (8) Apply this product two to three times.
[0128] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high-hardness glaze coating, characterized in that: In terms of mass percentage, it is prepared from the following raw materials: 20-30% fluorinated silicone acrylic emulsion, 5-20% potassium silicate liquid, 8-35% composite filler, 2-8% functional additive, 2-6% film-forming additive, 20-60% water; The composite filler is prepared using titanium dioxide, silicon dioxide, bentonite and attapulgite as raw materials.
2. A high-hardness glaze coating according to claim 1, characterized in that: The preparation of the composite filler includes the following steps: S1. Mix bentonite and attapulgite, crush and screen them, and then treat them with hydrochloric acid solution. After the treatment, filter, wash and dry them to obtain material I; S2, mixing the material I obtained in step S1 with sodium hydroxide and then subjecting it to high temperature treatment, after the treatment, obtaining material II; S3, adding the material II obtained in step S2 to an aqueous solution containing dodecylmethyl dihydroxyethyl ammonium bromide, and then treating it under heating conditions. After the treatment is completed, it is first centrifuged, washed, and dried, and finally activated; after the activation is completed, material III is obtained; S4, adding silicon dioxide to the solvent, and then adding succinic anhydride and KH550 after uniform dispersion, maintaining centrifugal stirring and heating treatment, after the treatment is completed, centrifugation, washing, and drying are performed to obtain material IV; S5. Add titanium dioxide, material III obtained in step S3 and material IV obtained in step S4 into water, stir under heating conditions, and after the treatment, filter, dry and grind to obtain a composite filler.
3. A high-hardness glaze coating according to claim 2, characterized in that: In step S1, the mass ratio of bentonite to attapulgite is 1:1.5-2.5, and the bentonite is sieved through 80-150 mesh; the concentration of the hydrochloric acid solution is 10-15wt%, the temperature of the hydrochloric acid solution treatment is room temperature, and the treatment time is 2-6h.
4. A high-hardness glaze coating according to claim 2, characterized in that: In step S2, the mass ratio of material I to sodium hydroxide is 1:0.3-0.65, the high temperature treatment temperature is 710-780°C, and the treatment time is 0.5-2h.
5. A high-hardness glaze coating according to claim 2, characterized in that: In step S3, the concentration of dodecylmethyldihydroxyethylammonium bromide is 4-8wt%, and the mass ratio of material II to dodecylmethyldihydroxyethylammonium bromide is 1:0.3-0.6; the heating treatment temperature is 50-70°C, and the treatment time is 1-6h; the activation treatment temperature is 100-110°C, and the activation time is 0.5-4h.
6. A high-hardness glaze coating according to claim 2, characterized in that: In step S4, the solvent is DMF, the mass ratio of silica, solvent, succinic anhydride and KH550 is 1:50-70:2-3.5:5-8; the centrifugal stirring rate is 80-150 rpm; the heating temperature is 30-40° C., and the treatment time is 1-6 h.
7. A high-hardness glaze coating according to claim 2, characterized in that: In step S5, the mass ratio of titanium dioxide, material III, and material IV is 1:0.4-0.7:0.5-0.9; the heating treatment temperature is 25-35°C, and the treatment time is 1-4h.
8. The high-hardness glaze coating according to claim 1, characterized in that: The functional additive is selected from one or more of a dispersant, a defoamer, an antifreeze agent, a wetting agent, a pH regulator, a preservative, a mildew preventer, a leveling agent, and a thickener.
9. A high-hardness glaze coating according to claim 8, characterized in that: The film-forming aid is selected from one or more of propylene glycol, ethylene glycol, and alcohol ester film-forming aids.
10. A method for preparing the high-hardness glaze coating according to any one of claims 1 to 9, characterized in that: The steps include: Mix half the weight of water, fluorinated silicone acrylic emulsion, potassium silicate liquid, functional additives and film-forming additives and stir evenly, then add the composite filler and the other half weight of water and stir evenly again.
Citation Information
Patent Citations
Resin for antifouling paint and preparation method thereof
CN106632876A
Outer wall inorganic glaze coating and preparation method thereof
CN110922795A
Sand-containing glaze coating as well as preparation method and application thereof
CN112795215A
Preparation and construction method of high-hardness polishable art coating
CN118440552A
Building external wall coating
CN104927504A